2012
DOI: 10.1074/jbc.m112.411454
|View full text |Cite
|
Sign up to set email alerts
|

Atg9 Vesicles Recruit Vesicle-tethering Proteins Trs85 and Ypt1 to the Autophagosome Formation Site

Abstract: Background: Atg9 vesicles are directly involved in autophagosome formation. Results: Mass spectrometric analysis revealed that Atg9 vesicles contain vesicle-tethering proteins Trs85 and Ypt1. These proteins localize to the autophagosome formation site in an Atg9-dependent manner. Conclusion: Atg9 vesicles play a role in the recruitment of the vesicle-tethering machinery. Significance: This study is the first proteomics study of Atg9 vesicles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
110
2
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(117 citation statements)
references
References 45 publications
4
110
2
1
Order By: Relevance
“…For example, ATG9 is able to recruit the vesicle tethering machinery, TRAPPIII complex and Ypt1, to the PAS whereas absence of ATG9 impairs the trafficking of Trs85 or Ypt1 onto the autophagosome membrane (44,45). It has also been shown that UVRAG, another component of the ER tethering complex, works together with the PI3K complex to mobilize ATG9 translocation during autophagosome formation (46).…”
Section: Discussionmentioning
confidence: 99%
“…For example, ATG9 is able to recruit the vesicle tethering machinery, TRAPPIII complex and Ypt1, to the PAS whereas absence of ATG9 impairs the trafficking of Trs85 or Ypt1 onto the autophagosome membrane (44,45). It has also been shown that UVRAG, another component of the ER tethering complex, works together with the PI3K complex to mobilize ATG9 translocation during autophagosome formation (46).…”
Section: Discussionmentioning
confidence: 99%
“…Immunoelectron microscopy analysis in another study detected Atg9 in clusters of small vesicles and tubules, and it was proposed that the isolation membrane may be initiated by the fusion of these clustered vesicles/tubules [89]. The Atg9 vesicle fusion mechanism may involve the yeast Rab protein Ypt1 and its GEF complex (the TRAPP III complex), which are required for autophagy and were identified in purified Atg9 vesicles [90,91]. In addition, SNARE proteins required for autophagosome formation in yeast have also been implicated in Atg9 vesicle fusion [92].…”
Section: Atg9 Vesicles As a Membrane Sourcementioning
confidence: 99%
“…The TRAPPIII complex associates withSec23, an integral component of COPII, and is a GTP Exchange Factor (GEF) of a small GTPase Ypt1 in yeast. Therefore COPII vesicles and Ypt1 are recruited to the PAS, where COPII vesicles supply membrane and Ypt1 regulates vesicular events [50,[74][75][76]. Furthermore, it is proposed that the TRAPPIII complex may also be a tether to facilitate heterotypic fusion between an Atg9 vesicle and a COPII vesicle in the PAS [50,77].…”
Section: Converging On the Pasmentioning
confidence: 99%
“…Together with the C-terminal EAT domain of Atg1,which senses membrane curvature, the Atg17/Atg29/Atg31 complex dimerizes and may act as a tether for two Atg9 vesicles to facilitate homotypic fusion possibly via SNARE proteins [52,65,73]. In addition to theAtg1/Atg13/ Atg17/Atg29/Atg31 complex, another tethering complex, the transport protein particle III (TRAPPIII), also translocate to the PAS through direct association with Atg9 and Atg17 via Trs85, a specific subunit of TRAPPIII [74,75]. The TRAPPIII complex associates withSec23, an integral component of COPII, and is a GTP Exchange Factor (GEF) of a small GTPase Ypt1 in yeast.…”
Section: Converging On the Pasmentioning
confidence: 99%